Spell Checking and Error Correcting System for text paragraphs written in Punjabi Language using Hybrid approach (International Journal of Engineering and Computer Science, 2014)
The spell checker is the basic necessity for composing any documentation in any language. Spell checker is software that analysis the incorrect word and provide their most possible correct word. Make a spell checker in Indian language is a very challenging and uphill task. Punjabi is world’s 14th mostly used language. Work done in Punjab language is very challenging task. In a computer system a Punjabi words is typed in different manners because Punjabi language has more than 40 different fonts. Punjabi is mother tongue for more than 110 million people in the world. This paper describes the techniques used in a spell checker. Natural language processing (NLP) is a field of computer science concerned with the interactions between computers and human (natural) languages. Modern NLP algorithms are based on machine learning, especially statistical machine learning.